Associations between the depressive symptoms, subjective cognitive function, and presenteeism of Japanese adult workers: a cross-sectional survey study - Kuniyoshi Toyoshima; Takeshi Inoue; Akiyoshi Shimura; Jiro Masuya; Masahiko Ichiki; Yota Fujimura; Ichiro Kusumi (BioPsychoSocial Medicine, 2020)
Abstract Background Presenteeism has attracted much attention in the research into mental health. However, how cognitive complaints and depressive symptoms affect presenteeism remains unknown. Therefore, this study examined the correlation between subjective cognitive impairment, depressive symptoms, and work limitations. Methods We collected data from 477 adult workers in Japan. We evaluated subjective cognitive function using the Cognitive Complaints in Bipolar Disorder Rating Assessment (COBRA), depressive symptoms with the Patient Health Questionnaire 9 (PHQ-9), and work limitations with the Work Limitations Questionnaire 8 (WLQ-8). The relations between depressive symptoms, cognitive complaints, and work limitations were examined using Spearman’s rank correlations and multiple regression analysis. It was hypothesized that cognitive complaints would mediate the effects of depressive symptoms on work productivity loss, which was tested using path analysis. Results The results indicated that cognitive complaints were significantly correlated with work limitations and depressive symptoms. Multiple regression analysis, using the WLQ-8 productivity loss score as the dependent variable, revealed that COBRA and PHQ-9 scores were significant predictors of work productivity loss. We performed path analysis using PHQ-9, COBRA, and WLQ-8 productivity loss scores and created a path diagram, which revealed that the direct effects of both depressive symptoms and cognitive dysfunction on work productivity loss were statistically significant. Moreover, depressive symptoms indirectly affected work productivity loss through subjective cognitive impairment. There was no significant interaction effect between depressive symptoms and cognitive complaints. Conclusions Our results suggest that work limitations may be predicted by not only depressive symptoms but also cognitive complaints. Moreover, subjective cognitive impairment may mediate the effect of depressive symptoms on presenteeism among adult workers.